Incidence and Trends of High Tibial Osteotomy and Unicompartmental Knee Arthroplasty Over the Past Decade: A Lost Art - Lacee K. Collins, BS; Timothy L. Waters, BA; Matthew W. Cole, MD; Cindy X. Wang, BS; Uwe R. Pontius, MD; Corrine Sommi, MD; William F. Sherman, MD, MBA (Arthroplasty Today, 2023)
Background: After failed nonoperative treatment, unicompartmental osteoarthritis can be treated surgically by either unicompartmental knee arthroplasty (UKA) or high tibial osteotomy (HTO). The purpose of this retrospective study is to analyze utilization and demographic trends of UKA and HTO relative to total knee arthroplasty (TKA) over the past decade. Methods: A retrospective review was conducted using the PearlDiver database. Patients that received a UKA or HTO were identified. Trend analyses of surgical procedure utilization were performed with the Mann-Kendall trend test. Demographic data and the rates of various comorbidities were also queried. Results: A total of 103,465 UKAs, 2183 HTOs, and 1,413,425 TKAs, between 2010 and 2021 quarter 1, were analyzed. Trend analyses revealed that relative to TKA utilization, UKA utilization significantly increased (P < .001) while HTO utilization significantly decreased (P < .001). The compound annual growth rate of UKA utilization relative to TKA was +5.16% from 2010 to 2017 but was −10.61% from 2018 to 2021, while that of HTO relative to TKA was −9.69% from 2010 to 2021. Demographic analyses demonstrated the UKA cohort (63.1) was significantly older than the HTO cohort (46.5) (P < .001). Additionally, there were significantly more female patients who underwent UKA than HTO (P < .001). Conclusions: The present study demonstrated that relative to TKA, UKA utilization increased from 2010 to 2017, with a subsequent decrease afterward, whereas HTO utilization decreased since 2010. Demographic differences exist between the 2 operations, with HTOs more commonly performed in younger male patients, and UKAs in older female patients. Level of Evidence: Level III.